PETROGEOCHEMICAL CHARACTERISTICS OF THE KIMBERLITES FROM THE MIDDLE MARKHA REGION WITH APPLICATION TO THE PROBLEM OF THE GEOCHEMICAL HETEROGENEITY OF KIMBERLITES - Lapin A.V.; Tolstov A.V.; Vasilenko V.B. (My University, 2007)
A comparative geochemical investigation of kimberlites from the Middle Markha region and traditional diamond-bearing areas of Yakutia supported the division of kimberlites into two geochemical types. One of them includes kimberlites from the traditional diamond-bearing areas of Yakutia, and the other is represented by the kimberlites of the Middle Markha region and the rocks of the Zolotitsa field and V. Grib pipe of the Arkhangelsk province. The obtained representative parameters of the two kimberlite types indicate a sharp geochemical contrast between them, and the individual features of correlation relationships between the elements in the rocks of the two types suggest that these differences are related to fundamental genetic factors, which concern primarily the group of highly charged incompatible trace and radioactive elements. The presence of geochemically contrasting rocks within a rather uniform petrochemical association and the geochemically specialized occurrences of kimberlites and related rocks are consequences of repeated metasomatic transformations of mantle rocks under the influence of deep-derived fluids or volatiles released during the recycling of subneous source and subsequent derivation of geochemically specialized types of deep magmas showing signatures of individual mantle sources.